0570 Tailored Approach To Sleep Health Education (TASHE): Preliminary Results For A Randomized Controlled Trial Of A Web-based Educational Tool To Promote Self-efficacy For Osa Diagnosis And Treatment Among Blacks. (27th April 2018) - Robbins, R; Allegrante, J; Rapoport, D M; Senathirajah, Y; Rogers, A; Williams, N; Cohalll, A; Butler, M; Ogedegbe, O; Jean-Louis, G
Abstract: Introduction: Blacks are at higher risk of developing obstructive sleep apnea (OSA), relative to other racial/ethnic groups. Yet, they are less likely to seek evaluation and treatment than their counterparts. In an NHLBI-funded study to promote awareness of OSA among blacks, we designed and evaluated the effect of a tailored, web-based educational intervention. Methods: We conducted a 6-month randomized controlled trial (n=200) of the Tailored Approach to Sleep Health Education (TASHE) versus generic OSA educational materials. The intervention comprised a web-based tool that incorporated health communication best practices, including message tailoring and narrative storytelling designed to promote awareness of OSA. Participants received a pre-programmed tablet providing access to either the TASHE or control website (National Sleep Foundation), and were asked to review the materials weekly. We recruited community-dwelling blacks from barbershops, health centers, and faith-based organizations and randomized individuals to TASHE or control. Primary outcomes were sleep hygiene and OSA self-efficacy (risk perception, outcome expectation, treatment efficacy), beliefs and knowledge. Of the sample, 46% were male and average age was 48.8 ± 13.1 years. Effects of the intervention were modeled using linear repeated-measures intent-to-treat mixed effects regression analysis with maximum likelihood estimation. Results: Sleep hygiene increased as a result of exposure to the TASHE intervention by approximately one unit per month, relative to the control group (b=0.95, SE=0.39, p=.015). Compared to the control group, those exposed to TASHE had increased sleep hygiene (5.68 units; 95%CI:1.11–10.25) over the 6-month period. Among the three dimensions of self-efficacy, treatment efficacy increased over time for participants in both groups (b=0.07, SE=0.03, p=.013). No significant changes in OSA beliefs or knowledge were observed. Conclusion: Our study showed the web-based tailored intervention led to improved sleep hygiene for blacks at high OSA risk. Further scale-up and dissemination of this intervention may enable a broader understanding of this approach for addressing health disparity in OSA. Support (If Any): Supported by grants R25HL116378, RO1MD007716 and K07AG052685.